Novel Perspectives on Thrombopoietin Receptor Agonists Applications - Stafylidis, Christos; Vlachopoulou, Dimitra; Syriopoulou, Stavroula; Chatzidavid, Sevastianos; Viniou, Nora-Athina (Hämostaseologie, 2024)
Second-generation thrombopoietin receptor agonists (TPO-RAs), romiplostim, eltrombopag, and avatrombopag, have been proved to be significant stimulators of megakaryopoiesis and, in the last decade, they have been incorporated in the treatment options against refractory immune thrombocytopenia in children and adults that do not respond to conventional therapy. Additionally, given their beneficial impact on hematopoiesis, they have successfully been applied in cases of non-immune thrombocytopenia, such as aplastic anemia, HCV-related thrombocytopenia, chronic liver disease, and most recently acute radiation syndrome. During the past years, a wide variety of clinical studies have been performed, in regard to the use of TPO-RAs in various thrombocytopenic settings, such as malignant hematology and hematopoietic stem cell transplantation, hereditary thrombocytopenias, and chemotherapy-treated patients with solid organ tumors. Although data indicate that TPO-RAs may be an effective and safe option for managing disease- or treatment-related thrombocytopenia in these patients, further research is needed to determine their efficacy and safety in these settings. Furthermore, recent studies have highlighted novel properties of TPO-RAs that render them as potential treatment candidates for reducing tumor burden or fighting infections. Herein, we discuss the potential novel applications of TPO-RAs and focus on data regarding their efficacy and safety in these contexts.
Keywords: eltrombopag; romiplostim; avatrombopag